Answer:
The answer is C) (6, -2).
Step-by-step explanation:
First, subtract both sides by y in the first equation, to figure out what x is.
x+y-y=4-y
x=4-y
x is equal to 4-y. Use substitution to plug that in to the second equation for x.
2x-3y=18
2(4-y)-3y=18
Now, solve for y. Expand.
2(4-y)-3y=18
8-2y-3y=18
Combine like terms.
8-2y-3y=18
8-5y=18
To get y by itself, subtract 8 from both sides.
8-8-5y=18-8
-5y=10
Lastly, divide both sides by -5.
-5/-5y=10/-5
y=-2
Since we know that y is equal to -2, we can solve for x in the equation x=4-y.
x=4-y
x=4-(-2)
*Negative & Negative makes a Positive*
x=6
Therefore, your answer is x being equal to 6, and y being equal to -2.
Hope this helped!